A Mobility-Aware and Sociality-Associate Computation Offloading Strategy for IoT. (28th June 2021) - Lu, Yanfei; Chen, Zengzi; Gao, Qinghe; Jing, Tao; Qian, Jin
Abstract : Mobile edge computing, a promising paradigm, brings services closer to a user by leveraging the available resources in an edge network. The crux of MEC is to reasonably allocate resources to satisfy the computing requirements of each node in the network. In this paper, we investigate the service migration problem of the offloading scheme in a power-constrained network consisting of multiple mobile users and fixed edge servers. We propose an affinity propagation-based clustering-assisted offloading scheme by taking into account the users' mobility prediction and sociality association between mobile users and edge servers. The clustering results provide the candidate edge servers, which greatly reduces the complexity of observing all edge servers and decreases the rate of service migration. Besides, the available resource of candidate edge servers and the channel conditions are considered to optimize the offloading scheme to guarantee the quality of service. Numerical simulation results demonstrate that our offloading strategy can enhance the data processing capability of power-constrained networks and reach computing load balance.